Oral Manifestations of Graft vs. Host Disease: A Comprehensive Review for Best Practice in Dentistry - Michele Miranda; Francesco Gianfreda; Danesi Carlotta; Sofia Armati; Alberta Barlattani; Patrizio Bollero (Medicina, 2023)
Graft-versus-host disease (GVHD) is a complication of hematopoietic stem cell transplantation (HSCT). GVHD may also develop following solid transplants or blood transfusions if white blood cells are transferred. GVHD affects multiple organs, including the oral tissues. This pictorial review provides a background of GVHD to dental practitioners, describes the most common oral manifestations of GVHD, and highlights the main treatment modifications needed to deliver dental care to patients with GVHD. A narrative review enriched with clinical data was performed by searching the scientific literature for all articles regarding GVHD and oral manifestations/therapies. All articles without exclusion criteria, except animal tests, were included in the above review. Acute GVHD may manifest in the oral mucosa; however, it often develops immediately following HSCT when routine dental treatment is postponed. Chronic GVHD may manifest in the oral mucosa, the salivary glands, and the musculoskeletal compartment. It may indirectly affect the teeth and the oral flora, putting the patient at risk for infections. Importantly, GVHD poses an increased risk for oral cancer. GVHD has a wide range of oral manifestations, some of which may affect dental treatment.